PENGGUNAAN BEKATUL FERMENTASI “Aspergillus Niger “ DALAM PAKAN TERHADAP KARAKTERISTIK ORGAN DALAM AYAM PEDAGING - Nonok Supartini; Eka Fitasari (BUANA SAINS, 2011)
The purpose of the research was to study the effect of Aspergillus rice bran fermentation on intestinal characteristic (pH, intestinal digest viscosity, proteolitic intestinal digest activity) and internal organs weights (liver, bile, pancreas). The materials used for this research were 96 Lohman broiler chicks with average initial body weight of 47,99 ± 4,93 g without difference on the sexes. The method used Complete Random Plan (RAL) with 4 treatments ie control (P0), control + 5% rice bran fermentation (P1), control + 10% rice bran fermentation (P2), and control + 15% rice bran fermentation (P3) with repeated 6 times. If there were significant influence it would be further tested with Duncan’s Multiple range Test (BNT). The result showed that treatments gave very significantly affected (P0.05) on internal organs. The conclusion is that the using of 15% rice bran fermentation gives the best result based on intestinal characteristics